Dosimetria Física e Controle de Qualidade em Radioterapia - Eberlin, Bárbara Büscher von Teschenhausen [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Radiotherapy is a multidisciplinary speciality which uses complex equipment and radiation sources for delivery of treatment, using high-energy ionizing radiation to treat cancer at several stages of complexity. Since radiation therapy is a technique which involves a precalculated radiation dose, it shall be established quality assurance programs that provide an efficient and safety treatment. The International Commission on Radiation Units and Measurements (ICRU) report No. 50 has recommended dose uniformity between 5% of the prescribed dose throughout the region of interest. This is one of the most primordial points that justify the importance of a suitable attendance of the equipments quality and performance. For quality control, the medical physicist will be involved with establishing and running a Quality Control Program (QCP). He must adapt or develop the procedures of equipment acceptance and commissioning, besides verifying the use of principles and accepted protocols of national and international reports to assure the correct quality, quantity, and placement of radiation during the performance of a radiological procedure, establishing adequate protocols to ensure accurate patient dosimetry. This present work consists of a description of the activities carried through the Sectors of Radiation Therapy of the Hospital of Clinics of the Campinas State University (Unicamp), particularly in the implementation of the Quality Control Program

A Radioterapia é uma especialidade médica que utiliza radiação ionizante para tratamento, desde lesões na pele até tumores de diversos graus de complexidade. Por ser uma técnica que envolve a aplicação de uma dose pré-calculada de radiação ionizante, devem ser estabelecidos e implementados programas de controle de qualidade com a finalidade de assegurar um tratamento eficaz e seguro ao paciente. Recomenda-se uma uniformidade de dose na região de interesse dentro de 5% da dose prescrita pelo médico (ICRU Report No. 50), sendo este um dos principais pontos que justificam a importância de um acompanhamento adequado da qualidade e do desempenho dos equipamentos. A responsabilidade principal da execução do Programa de Garantia da Qualidade (PGQ) é do Físico Médico, o qual deve adaptar ou desenvolver os procedimentos de aceitação e comissionamento dos equipamentos, além de estabelecer e realizar controles de qualidade periódicos que verificam se os valores de referência estão dentro das margens aceitáveis de protocolos e normas nacionais e internacionais. O presente trabalho consiste da realização e descrição das atividades realizadas nos Setores de Radioterapia do Hospital de Clínicas da Universidade Estadual de Campinas (Unicamp), particularmente na implementação do Programa de Garantia da Qualidade
Keywords: Radioterapia